Pesantren Based on Child-Friendly: Countering the Bullying Cases in Pesantren - Arina Zulva, Dina Arvi; Yahya, Imam; Rofiq, Ahmad (Santri: Journal of Pesantren and Fiqh Sosial, 2024)
The existence of violence in the learning process is one of the factors that influences the comfort of each Santri. Nothing but the comfort of a Santri at Pesantren. Every learning process needs to pay attention to a child's rights and needs so that they can be met. Both in terms of security and comfort. The learning process must also proceed in a dignified and humane manner. However, the increasing violence that occurs in Pesantren is one of the reasons for the need to create Pesantren education that is child-friendly by ensuring safety and health. Therefore, this article aims to analyze the implementation of child-friendly Pesantren programs. This research uses a case study approach at the Pesantren Al-Anwar-4 Sarang and Alhamdulillah Kemadu Rembang. The analysis results show that child-friendly Pesantren can be achieved by implementing a positive discipline program for each Pesantren community, from caregivers, coaches, teachers, and Santri. As the learning process progresses, humanist teachers are the key to the success of child-friendly education in Pesantren by guiding Santri, motivating them, appreciating their strengths and weaknesses, and developing various new ideas and insights about learning along with developments in science and technology, as in the trials implemented at Al-Anwar-4 and Alhamdulillah by implementing positive discipline to prevent violence in Pesantren. This trial had a significant positive effect.